ADVANCED MATHEMATICS FORM 5 – ALGEBRA

Share this post on:

Indices (law of exponents)

Three basic rules including the Indices are:

            i) am x an = am + n

            ii) am ÷ an = am – n

            iii) (am) n = am

Negative indices

Consider a5 ÷ a2 = a5
– 2 = a3                                                                                                                        

                        = a2 ÷ a5 = a2
– 5 = a -3 

edu.uptymez.comedu.uptymez.comedu.uptymez.comIn general

edu.uptymez.com                        a -m = edu.uptymez.com

Fractional indices

Consider edu.uptymez.com

edu.uptymez.com

Similarly

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

Zero exponents

Consider am x ao = am + o

                        edu.uptymez.comao = 1

Laws of logarithm

If a and b are two positive numbers there exist a third number c such that 

ac = b

            →c is the logarithm of b to base a

            i. e edu.uptymez.com = c

            edu.uptymez.com

Definition

Logarithm of ‘x’ to base ‘a’ is the power to which ‘a’ must be raised to give ‘x’.

If p = edu.uptymez.com and q =edu.uptymez.com, then edu.uptymez.com= x and edu.uptymez.com = y

Thus

1.      edu.uptymez.comedu.uptymez.com
edu.uptymez.com
edu.uptymez.com

2.      edu.uptymez.comedu.uptymez.com
edu.uptymez.com
edu.uptymez.com

3.      edu.uptymez.comedu.uptymez.com
edu.uptymez.com
edu.uptymez.com

Change of base

If y = edu.uptymez.comedu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

edu.uptymez.com

EXAMPLE

1.                  Solve for x, edu.uptymez.com

Solution

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

edu.uptymez.com
edu.uptymez.com

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

Note that:

There are two important bases of logarithms

10 and e

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

Series

A series is the sum of a sequentially ordered finite or infinite set of terms

Finite series

      Is the one have defined first and last term e.g. 1 + 3 + 5 + 7 + 9 + 11…… + 21 is a finite series

Infinite series

      Is the one have defined the first but not the last term e.g. 1 + 3+ 5+ 7+ 9+ 11+ …..

In both cases the first term is 1

The sigma notation

∑ stands for ” sum of ”

edu.uptymez.com

e.g.

edu.uptymez.com

edu.uptymez.com
edu.uptymez.com

Exercise

Discuss the following  and find the sum if n = 8

edu.uptymez.com

edu.uptymez.com

The sum of the first n natural numbers

edu.uptymez.com
edu.uptymez.com

The sum of squares of the first n natural numbers

edu.uptymez.com
edu.uptymez.com

The sum of the cubes of the first n natural numbers

edu.uptymez.com
edu.uptymez.com

edu.uptymez.com

Example

                                I.    If an = n2 + 3n + 1 determine an expression for n        

edu.uptymez.com             

                             II.     If an = n3 + 2n2 + 4n evaluate

a) a1    b) a4    c)edu.uptymez.com                                                                   

The sum of the first n natural numbers

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

The sum of the squares of the first n natural numbers

edu.uptymez.com

Proof,

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

Exercise

1.       Evaluate       edu.uptymez.com

Proof by the mathematical induction

Example

            Prove that n (n2 + 5) is exactly divisible by 3 for all positive integers n

Proof: I

            Let n = 1;          1(12 + 5) = 6 = 3 x 2

                        n = 2;       2 (22 + 5) = 18 = 3 x 6

                        n = 3;      3 (32 + 5) = 42 = 3 x 14

                        n = 4;       4 (42 + 5) = 84 = 3 x 28

                        n = 7;        7 (72 + 5) = 378 = 3 x 126

Proof: II

                i) Let n = 1 = 1 (12 + 5) = 6 = 3 x 2

               ii) Let n (n2 + 5) be divisible for n = k

                        i.e. k (k2 + 5) = 3p, where p is any integers

               iii) When n = k + 1

                        (k + 1) ( (k +1)2 + 5) = (k + 1) (k2 + 2k + 1 + 5)

                                                           = (k + 1) ((k2 + 5) + (2k + 1))

                                                           = k (k2 + 5) + k (2k + 1) + (k2 + 5) + (2k +1)

                                                           = 3p + 2k2 + k + k2 + 5 + 2k +1

                                                           = 3p + 3k2 + 3k + 6

                                                           = 3 (p + k2 + k + 2)

Since p and k are positive integers

So the number in the bracket is positive

            iv) Since when n = 1 the values 1 (12 + 5) is divisible by 3 then the value n (n2 + 5) will be divisible by 3 for n = 2, n = 3, n = 4…… by the above  working

            →n (n2 + 5) is divisible by 3 for all    n
edu.uptymez.com+

Principle of proof by mathematical induction

It states if s1, s2, s3…..Sn…. is a sequence of statements and if

                                                    i) s1 is true

                                                    ii) Sn → Sn + 1, n = 1, 2, 3 … are true, then s1, s2, s3…… Sn… are true statement

Examples

1.  Prove by mathematical induction that 2 + 4+ 6 +…..2n = n (n + 1)

            Solution

            When n = 1

                        L. H. S = 2, R. H. S = 1(1 + 1) = 2

                        L. H.S = R. H. S

            It is true for n = 1

Let the statement be true for n = k

            2 + 4 + 6 + …. 2k = k (k + 1)

Required to prove when n = k + 1

2 + 4 + 6 + …… 2k + 2(k + 1) = k (k + 1) + 2(k + 1)

                                                           = k2 + k + 2k + 2

                                                           = k2 + 3k + 2

                                                           = k2 + k + 2k + 2

                                                           = k (k + 1) + 2 (k + 1)

                                                           = (k + 1) (k + 2)

Which is the same as putting n = k + 1 in the formula

Since n = 1gave a true statement, n =2, n = 3, n = 4… will be true statement as worked above

2.   2. Prove by induction that edu.uptymez.com

            Solution

            Proof:            

            When n = 1, edu.uptymez.com

            Also n = 1 giveedu.uptymez.com

                                   L.H.S = R. H. S

            Let the statement be true for n =k

            Let      edu.uptymez.com

Required to prove when n = k + 1

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

            Which is the same as putting n = k + 1 in the form

            Since n = 1 gave a true statement

            n = 2, n = 3, n = 4… will give true statement

3. Prove that  edu.uptymez.com

            Solution

            Proof:

                        When n = 1

                        L.H. S = 3 x 1 – 2 = 1

                        R.H.S = edu.uptymez.com                                                                                            

                        L.H.S = R.H.S

            Let the statement be true for n = k                      

            I.e. edu.uptymez.com        required to prove when n = k + 1

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

            Which is the same as putting n = k + 1 in the formula since n = 1 gave a    true statement,

            n =2, n = 3, n = 4 … will give true statement

Share this post on: